Historical Analysis at The Javanese Speech Level - Lailatul, Shofi; Eria Fara Diva, (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Javanese is one of the largest regional languages ​​in Indonesia and possesses a unique categorization system, namely speech levels. In everyday use, Javanese is divided into three speech levels: Ngoko, Krama, and Krama Inggil. Furthermore, the use of these three speech levels also differs according to their levels. This article aims to examine the history of the formation of Javanese speech level categorization and the factors that influence it. The method used is a literature study with a historical and sociolinguistic approach. The results of the study indicate that the Javanese speech level system was developed not only linguistically but was also heavily influenced by the social structure of Javanese society, particularly in the context of feudalism and palace culture. In the modern era, this system has shifted due to globalization, education, and changes in societal communication patterns.